Architecting enterprise blockchain solutions - Holbrook, Joseph (Sybex, 2020)
Demystify architecting complex blockchain'applications in enterprise environments Architecting Enterprise Blockchain Solutions'helps engineers and IT administrators understand how to architect complex blockchain'applications in enterprise environments. The book takes a deep dive into the intricacies of supporting and securing blockchain technology, creating and implementing decentralized applications, and incorporating blockchain into an existing enterprise IT infrastructure. Blockchain is a technology that is experiencing massive growth in many facets of business and the enterprise. Most books around blockchain primarily deal with how blockchains are related to cryptocurrency or focus on pure blockchain development. This book teaches what blockchain technology is and offers insights into its current and future uses in high performance networks and complex ecosystems.-'Provides a practical, hands-on approach -'Demonstrates the power and flexibility of enterprise blockchains such as Hyperledger and R3 Corda -'Explores how blockchain can be used to solve complex IT support and infrastructure problems -'Offers numerous hands-on examples and diagrams Get ready to learn how to harness the power and flexibility of enterprise blockchains!